Structural investigation of As-Se chalcogenide thin films with different compositions: formation, characterization and peculiarities of volume and near-surface nanolayers - Kondrat, O.; Holomb, R.; Mitsa, V.; Veres, M.; Tsud, N. (Functional Materials, 2017)
As₂₀Se₈₀, As₄₀Se₆₀ and As₅₀Se₅₀ films were studied by Raman spectroscopy in order to examine the local- and medium-range order of the structure. In addition, X-ray photoelectron, Raman and surface enhanced Raman spectroscopy were used to characterize the structural peculiarities at the top surface of As-Se nanolayers. Raman investigations reveal the dominance of the As₂Se₃ and As₄Se₄ molecules in the volume of the As₄₀Se₆₀ and As₅₀Se₅₀ films and significant contribution of Se in the structure of the As₂₀Se₈₀ film. The composition and local structure of the surfaces were determined by curve fitting of the experimental X-ray photoelectron As 3d and Se 3d core level spectra. A significant Se-enrichment was found at the near-surface layers in comparison with the composition of deeper layers which is confirmed by the dominance of As-3Se structural units in all compositions. This enrichment was also observed by surface enhanced Raman spectroscopy. Processes of arsenic oxidation and desorption of the oxidized products are impacting the structure of the surface layers of As₂₀Se₈₀, As₄₀Se₆₀ and As₅₀Se₅₀ films.